Experimental Woodsmoke Exposure During Exercise and Blood Oxidative Stress. Issue 12 (December 2018) - Peters, Bridget; Ballmann, Christopher; Quindry, Tiffany; Zehner, Emily G.; McCroskey, Justin; Ferguson, Matthew; Ward, Tony; Dumke, Charles; Quindry, John C.
Abstract : Objectives: The current laboratory study quantified blood oxidative stress to woodsmoke exposure. Methods: Participants inhaled woodsmoke during three randomized crossover exercise trials (Clean Air [0 μg/m 3 ], Low Exposure [250 μg/m 3 ], and High Exposure [500 μg/m 3 ], Woodsmoke [particulate matter less than 2.5 μm, PM2.5 ]). Trolox equivalent antioxidant capacity (TEAC), uric acid (UA), 8-isoprostanes (8-ISO), lipid hydroperoxides (LOOH), protein carbonyls (PC), nitrotyrosine (3-NT), 8-isoprostane, and myeloperoxidase (MPO) were quantified in Pre, immediately Post, and 1- (1Hr) hour post blood samples. Results: UA decreased following Low Exposure, while plasma TEAC levels increased Post and 1Hr. LOOH levels decreased 1Hr Post (High Exposure), while 8-Iso increased following both smoke trials. PC and MPO were unchanged following all trials, while 3-NT increased over Clean Air. Conclusion: Blood oxidative stress occurred largely independent of PM2.5 concentrations. Future studies should employ longer duration smoke and exercise combined with physiologic parameters.